Digital marketing communication for archery sports equipment on Instagram @vienetharcheryofficial - Putranto, Teguh Dwi; Vallejo, Ephraim Theodore S. (Jurnal Studi Komunikasi, 2022)
The sports equipment business is one of the businesses that is currently starting to develop. Supported by the desire of the community to engage in sports, one of which is archery, Vieneth Archery Official, one of the archery equipment shops, takes advantage of this situation. The purpose of this study was to digitally determine the marketing communication of archery sports equipment on Instagram @vienetharcheryofficial. The method used in this research is Krippendorff content analysis which is carried out by collecting data on the Instagram account @vienetharcheryofficial from 1 May 2022 to 30 May 2022. The conclusion of this study shows that Vieneth Archery, as an archery equipment shop, carries out digital marketing communications through @vienetharcheryofficial Instagram posts dominated by public relations and publicity efforts.